Assessing Tunisian Exports towards the European Union: Intensity, Complementarity and Gravity Estimation - CHAABOUNI, Karim (Asian Journal of Economic Modelling, 2022)
The Tunisian economy faces various challenges. Within a local and international environment full of constraints, several defies call to missing requirements like economic growth, employment, balance of payments’ equilibrium, etc… Despite these concerns, Tunisian economy remains open to the Rest of the World. Openness is consolidated since decades by Tunisian membership in the World Trade Organization (WTO), as well as by the country’s regional integration with various partners. In this field, the major involvement in world markets is confirmed by the Association Agreement (AA) concluded between Tunisia and the European Union (EU) in 1995, which launched and established a Free Trade Area (FTA) covering industrial products. Indeed the Tunisian trade remains strongly linked to EU and such links are expected to be reinforced since Tunisia and the EU have currently negotiated over the expansion of the FTA to agriculture and services within a project of Deep and Comprehensive Free Trade Agreement (DCFTA). The purpose of this paper is to focus on Tunisian exports towards the EU by assessing both the intensity and the complementarity of the trade side “from Tunisia to the EU”. Besides, by considering the Gravitational model, the aim of this paper is to identify the determinants of orienting Tunisian exports towards the EU. The findings highlight the concentration of Tunisian exports towards few EU countries despite a middle trade compatibility with all EU countries. Gravity estimation results, in line with previous works, point out the key roles of language and geographical proximity.